Reduced graphene oxide and organic silicon composite film and preparation method thereof
Through the preparation of the composite film of reducing graphene oxide and silicone, the network structure is formed by cross-linking and hydrolysis condensation reaction, and combined with the thermal coating technology, the swelling problem of graphene oxide nanosheet reverse osmosis membrane is solved, and the water flux and Salt retention rate ensures the long-term stability of the membrane and efficient desalination performance.
Patent Information
- Application Number
- CN202411284154.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-13
- Publication Date
- 2024-12-27
AI Technical Summary
The reverse osmosis membranes prepared by existing graphene oxide nanosheets are prone to swelling in water, resulting in reduced stability and reduced membrane flux, affecting the performance of desalination applications.
The preparation method of reducing graphene oxide and silicone composite film is adopted to form a two-dimensional and three-dimensional network structure through cross-linking reaction and hydrolysis condensation reaction. The thermal coating method is used to form a film layer with uniform thickness and smooth surface on the ceramic support body, which improves the Film stability and separation properties.
The increase in water flux (≥7.0L/(m2 h bar) and salt retention rate (≥97.2%) during the desalination process were achieved, and the long-term stability of the membrane structure was maintained under high NaCl content.
Smart Images

Figure CN119186283A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of reverse osmosis membranes, and mainly to a reduced graphene oxide and organic silicon composite membrane and a preparation method thereof. Background Art
[0002] Graphene has attracted widespread attention due to its high specific surface area and excellent electrical, thermal, optical and mechanical properties, especially in the field of water treatment.
[0003] Among them, graphene oxide (usually represented by GO) is a derivative of graphene. Similar to graphene, it contains a large number of oxygen-containing functional groups. Its unique structure and surface characteristics show potential application value in the field of water treatment. However, since the reverse osmosis membrane prepared by GO (graphene oxide) nanosheets is indeed prone to swelling during application, it not only reduces the stability of the reverse osmosis membrane, but also causes its interlayer structure to become loose, thereby reducing the membrane flux and affecting the application of reverse osmosis membrane in desalination. Summary of the invention
[0004] The object of the present invention is to provide a reduced graphene oxide and organosilicon composite membrane and a preparation method thereof, so as to solve the problem that the reverse osmosis membrane prepared in the prior art is prone to swelling in water, thereby affecting the stability and performance in desalination applications.
[0005] In order to solve the above technical problems, the present invention provides a method for preparing a reduced graphene oxide and an organosilicon composite film.
[0006] Take reduced graphene oxide, a silicon source precursor and an acidic catalyst in a mass ratio of 1: (0.6-1.5): 0.2, add the reduced graphene oxide and the silicon source precursor into tetrahydrofuran, then add the acidic catalyst to carry out a cross-linking reaction, the temperature of the cross-linking reaction is 70° C.-80° C., the reaction time is 7h-8h, and the solvent tetrahydrofuran in the mixed solution obtained after the cross-linking reaction is replaced with an alcohol solution to obtain a pre-cross-linked sol;
[0007] According to the mass ratio of the silicon source precursor, water and the acid catalyst of 1: (60-90): (0.1-0.2), the pre-crosslinked sol and the silicon source precursor are added into an alcohol solution, and then the water and the acid catalyst are added to carry out a hydrolysis condensation reaction, wherein the temperature of the hydrolysis condensation reaction is 40° C. to 60° C., the reaction time is 2 h to 4 h, and a mixed sol is obtained after the reaction;
[0008] Cutting a ceramic tube, pre-treating the ceramic tube, and then coating a particle layer and an intermediate layer to obtain a ceramic support body;
[0009] The mixed sol is rubbed on a ceramic support by a rubbing method, and is calcined to obtain a reduced graphene oxide and organic silicon composite film.
[0010] In one embodiment, the preparation method of the reduced graphene oxide is as follows:
[0011] The graphene oxide nano-dispersion liquid is placed in a drying device for hydrothermal reduction reaction. After the reaction is completed, a mixed solution is obtained. The mixed solution is washed with tetrahydrofuran and centrifuged to obtain the reduced graphene oxide.
[0012] In one embodiment, the length of the graphene oxide in the graphene oxide nano-dispersion is 5 um to 10 um.
[0013] In one embodiment, the temperature of the hydrothermal reduction reaction is 200° C. to 250° C.; the time of the hydrothermal reduction reaction is 2 h to 10 h.
[0014] In one embodiment, the centrifugal speed is 10000 rpm to 12000 rpm, the centrifugal time is 20 min to 30 min, and the number of centrifugal replacements is 2 to 3 times.
[0015] In one embodiment, the silicon source precursor includes at least one of hydroxymethyltriethoxysilane, aminopropyltriethoxysilane and 1,2-bis(triethoxysilyl)acetylene.
[0016] In one embodiment, the acidic catalyst is any one of hydrochloric acid, sulfuric acid and nitric acid.
[0017] In one embodiment, the alcohol solution is any one of an ethanol solution and a n-propanol solution.
[0018] In one embodiment, the replacement is performed by centrifugal replacement, the centrifugal speed is 6000 rpm to 12000 rpm, the centrifugal time is 20 min to 30 min, and the number of centrifugal replacements is 3 to 5 times.
[0019] In one embodiment, the ceramic tube is an α-Al2O3 asymmetric ceramic tube, the ceramic tube is a porous structure, and the pore size of the porous structure is 200-220 nm.
[0020] In one embodiment, the pretreatment includes grinding and boiling the ceramic tube.
[0021] In one embodiment, the particle layer is aluminum oxide, the particle size in the particle layer is 0.2μm~0.4μm, 4~5 layers are coated, the drying temperature is 200℃~220℃, the drying time is 20min~30min, the calcination temperature is 520℃~580℃, and the calcination time is 20min~25min.
[0022] In one embodiment, the intermediate layer is a silica-zirconia particle sol, which is coated with 9 to 10 layers, and the calcination temperature is 520° C. to 580° C., and the calcination time is 20 min to 25 min.
[0023] In one embodiment, the rubbing coating method is a hot coating method, the rubbing times are 2 to 3 times, the rubbing temperature is 150° C. to 200° C., and the calcination time is 20 min to 30 min.
[0024] The present invention also provides a reduced graphene oxide and organic silicon composite film, wherein the reduced graphene oxide and organic silicon composite film are prepared by the preparation method as described above.
[0025] Beneficial effects:
[0026] In the preparation method of the present invention, the reduced graphene oxide dispersion and the silicon source precursor are first subjected to cross-linking reaction to obtain a pre-cross-linked sol, and then the organosilicon network structure is cross-linked by hydrolysis and condensation reaction. Among them, compared with graphene oxide, it has more stable performance in desalination applications; moreover, the reduced graphene oxide dispersion and the silicon source precursor are cross-linked to form a two-dimensional water molecule rapid mass transfer channel, and then the organosilicon network structure is cross-linked by hydrolysis and condensation reaction, and the smooth surface of the reduced graphene oxide is used to improve the transmission speed of water molecules in the channel, and the selectivity of the rapid transmission of the reduced graphene oxide nanosheets and the bridging organosilicon network is coordinated to jointly improve the separation performance of the hybrid membrane. On the other hand, since the surface of the silicon source precursor sol contains a large number of hydroxyl functional groups, it is easy to agglomerate in water to form an amorphous network structure, which is easy to affect the performance of the composite membrane. The reduced graphene oxide and organosilicon composite membrane are prepared on the ceramic support by rubbing method, and the sol is quickly extended on the ceramic support, and the solvent is volatilized, which is conducive to the formation of a hybrid membrane with uniform thickness and smooth surface.
[0027] The reduced graphene oxide and organosilicon composite membrane prepared by the present invention has good water flux (≥7.0L / (m2 h bar)) and salt retention rate (NaCl: ≥97.2) in desalination applications, and the membrane structure is long-term stable during the desalination treatment process with a NaCl content of 2000-10000ppm. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1It is a schematic flow chart of the method for preparing reduced graphene oxide and organic silicon composite film in the present invention;
[0029] Figure 2 It is a mechanism diagram of the thermal rubbing method for reducing graphene oxide and organic silicon composite film in the present invention.
[0030] Figure 3 is a surface SEM image of the reduced graphene oxide and the organosilicon composite film of the present invention;
[0031] Figure 4 is a cross-sectional SEM image of the reduced graphene oxide and organosilicon composite film of the present invention;
[0032] Figure 5 This is a thermal stability test diagram of the reduced graphene oxide and organic silicon composite film in the present invention. DETAILED DESCRIPTION
[0033] The technical scheme of the present invention will be clearly and completely described below in conjunction with specific embodiments, but it will be appreciated by those skilled in the art that the following described embodiments are part of embodiments of the present invention, rather than all embodiments, and are only used to illustrate the present invention, and should not be considered as limiting the scope of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work, all belong to the scope of protection of the present invention. If specific conditions are not indicated in the embodiments, they are carried out according to normal conditions or conditions recommended by the manufacturer. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0034] As used herein, the term "prepared from" is synonymous with "comprising". As used herein, the terms "comprising", "including", "having", "containing" or any other variation thereof, are intended to cover a non-exclusive inclusion. For example, a composition, process, method, article, or apparatus that comprises the listed elements is not necessarily limited to only those elements but may include other elements not expressly listed or inherent to such composition, process, method, article, or apparatus.
[0035] When an amount, concentration, or other value or parameter is expressed as a range, a preferred range, or a range defined by a series of upper preferred values and lower preferred values, this should be understood as specifically disclosing all ranges formed by any pairing of any range upper limit or preferred value with any range lower limit or preferred value, regardless of whether the range is disclosed separately. For example, when a range of "1 to 5" is disclosed, the described range should be interpreted as including ranges "1 to 4", "1 to 3", "1 to 2", "1 to 2 and 4 to 5", "1 to 3 and 5", etc. When a numerical range is described in this article, unless otherwise stated, the range is intended to include its end values and all integers and fractions within the range.
[0036] In these examples, parts and percentages are by mass unless otherwise indicated.
[0037] "Parts by mass" refers to the basic unit of measurement for expressing the mass ratio of multiple components. 1 part can represent any unit mass, such as 1g or 2.689g. If we say that the mass of component A is a parts and the mass of component B is b parts, it means the ratio of the mass of component A to the mass of component B is a:b. Alternatively, it means that the mass of component A is aK and the mass of component B is bK (K is an arbitrary number, indicating a multiple factor). It should not be misunderstood that, unlike the mass parts, the sum of the mass of all components is not limited to 100 parts.
[0038] Graphene oxide (usually denoted as GO) is a derivative of graphene. Similar to graphene, it contains a large number of oxygen-containing functional groups. Its unique structure and surface characteristics show potential application value in the field of water treatment. However, since the reverse osmosis membrane prepared by GO (graphene oxide) nanosheets is indeed prone to swelling in application, its interlayer structure becomes loose, the resistance of water molecules passing through the membrane increases, thereby reducing the membrane flux.
[0039] In order to solve the above technical problems, preferred embodiments of the present invention are now described in detail with reference to the accompanying drawings.
[0040] Figure 1 A schematic diagram of the process for preparing a reduced graphene oxide and an organosilicon composite film is shown, see Figure 1 The method for preparing the reduced graphene oxide and organic silicon composite film comprises the following steps:
[0041] S1. Placing the graphene oxide nano-dispersion liquid in a drying device for hydrothermal reduction reaction. After the reaction is completed, a mixed solution is obtained. The mixed solution is washed with tetrahydrofuran and centrifuged to obtain the reduced graphene oxide.
[0042] Specifically, the graphene oxide nanodispersion liquid is a product that can be directly purchased on the market. The graphene oxide nanodispersion liquid refers to a liquid medium in which graphene oxide nanosheets are uniformly dispersed in water or an organic solvent, and the length of the graphene oxide contained in the graphene oxide nanodispersion liquid is 5 um to 10 um.
[0043] Furthermore, the drying device may be an air drying oven, that is, after the graphene oxide nano-dispersed is placed in the reactor, the reactor may be placed in an air drying oven for hydrothermal reduction reaction. The hydrothermal reduction reaction step can remove oxygen-containing functional groups in the graphene oxide, thereby reducing the graphene oxide to obtain reduced graphene oxide.
[0044] Specifically, the temperature of the hydrothermal reduction reaction is 200° C. to 250° C., and the time of the hydrothermal reduction reaction is 2 h to 10 h. It should be noted that different hydrothermal reduction times can be selected to prepare reduced graphene oxide with different reduction degrees.
[0045] In the hydrothermal reduction reaction, the oxygen-containing functional groups in graphene oxide are removed, which is beneficial for the prepared reduced graphene oxide to reduce the hydrogen bonding effect with water molecules, thereby reducing the possibility of swelling and further enhancing its stability.
[0046] Then, after the hydrothermal reduction reaction is completed, tetrahydrofuran is used to wash and the mixed solution is centrifuged. After the mixed solution is centrifuged, the upper layer is a liquid phase, and the solid phase of the lower layer is the reduced graphene oxide.
[0047] Among them, tetrahydrofuran is used as a solvent, and washing with tetrahydrofuran is beneficial to extracting reduced graphene oxide in the mixed solution.
[0048] Specifically, the centrifugal speed is 10000 rpm to 12000 rpm, the centrifugal time is 20 min to 30 min, and the number of centrifugal replacements is 2 to 3 times.
[0049] S2. Take reduced graphene oxide, silicon source precursor and acidic catalyst in a mass ratio of 1: (0.6-1.5): 0.2, add the reduced graphene oxide and silicon source precursor into tetrahydrofuran, and then add the acidic catalyst for cross-linking reaction. The temperature of the cross-linking reaction is 70°C-80°C, and the reaction time is 7h-8h. Replace the solvent tetrahydrofuran in the mixed solution obtained after the cross-linking reaction with an alcohol solution to obtain a pre-cross-linked sol.
[0050] The silicon source precursor may be at least one of hydroxymethyltriethoxysilane, aminopropyltriethoxysilane and 1,2-bis(triethoxysilyl)acetylene.
[0051] Preferably, the silicon source precursor is hydroxymethyltriethoxysilane.
[0052] The acidic catalyst may be any one of hydrochloric acid, sulfuric acid and nitric acid. That is, the reduced graphene oxide and the silicon source precursor may undergo a cross-linking reaction under the action of hydrochloric acid, sulfuric acid or nitric acid, and the reduced graphene oxide and the silicon source precursor may be preliminarily combined through the cross-linking reaction.
[0053] Specifically, the cross-linking reaction of the reduced graphene oxide and the silicon source precursor is carried out under stirring conditions.
[0054] The temperature of the cross-linking reaction is 70° C. to 80° C., and the reaction time is 7 h to 8 h. Under this reaction condition, it is beneficial to improve the cross-linking degree of the reduced graphene oxide and the silicon source precursor.
[0055] Furthermore, the solvent tetrahydrofuran in the mixed solution obtained after the cross-linking reaction can be replaced with an alcohol solution by a centrifugal replacement method, and the alcohol solution is conducive to the smooth progress of subsequent reactions.
[0056] Specifically, the centrifugal speed is 6000 rpm to 12000 rpm, the centrifugal time is 20 min to 30 min, and the number of centrifugal replacements is 3 to 5 times.
[0057] Specifically, the alcohol solution may be any one of an ethanol solution and a n-propanol solution.
[0058] For example, the chemical reaction formula of reduced graphene oxide and 1,2-bis(triethoxysilyl)ethylene (BTESEthy) added to tetrahydrofuran for cross-linking reaction is as follows:
[0059]
[0060] S3. According to the mass ratio of silicon source precursor, water and acid catalyst of 1: (60-90): (0.1-0.2), the pre-crosslinked sol and silicon source precursor are added into an alcohol solution, and then water and an acid catalyst are added to carry out a hydrolysis condensation reaction. The temperature of the hydrolysis condensation reaction is 40°C-60°C, and the reaction time is 2h-4h. After the reaction, a mixed sol is obtained.
[0061] The silicon source precursor may be the same material as that in S2, and the silicon source precursor may be at least one of hydroxymethyltriethoxysilane, aminopropyltriethoxysilane and 1,2-bis(triethoxysilyl)acetylene.
[0062] Preferably, the silicon source precursor is hydroxymethyltriethoxysilane.
[0063] The acidic catalyst can be any one of hydrochloric acid, sulfuric acid and nitric acid. That is, the silicon source precursor and water can undergo hydrolysis and condensation reaction under the catalytic action of the acidic catalyst to form a three-dimensional network structure, so that the original graphene oxide can be firmly embedded therein.
[0064] Specifically, the pre-crosslinked sol and the silicon source precursor are added to the alcohol solution, stirred for a preset time, and then deionized water is added dropwise. After continuing to stir for a preset time, an acidic catalyst is added dropwise for hydrolysis condensation reaction. The reaction temperature is controlled at 40°C to 60°C, and the reaction time is 2h to 4h. After the reaction, a mixed sol is obtained.
[0065] It should be noted that the selection of reduced graphene oxide and silicon source precursors for "pre-crosslinking" can improve the stability of reduced graphene oxide, thereby forming a two-dimensional rapid mass transfer channel for water molecules, and then cross-linking the silicone network structure through hydrolysis and condensation reaction. On the basis of pre-crosslinking, a three-dimensional stable mass transfer channel is constructed. The friction between carbon atoms and water molecules is relatively small. Therefore, the smooth surface of reduced graphene oxide is used to increase the transmission speed of water molecules in the channel, and the rapid transmission of reduced graphene oxide and the selectivity of the bridging silicone network are synergistically improved to jointly improve the separation performance of the hybrid membrane.
[0066] For example, the chemical reaction formula for the hydrolysis condensation reaction of 1,2-bis(triethoxysilyl)ethylene (BTESEthy), water and hydrochloric acid is as follows:
[0067]
[0068] Figure 2 The mechanism diagram of thermal rubbing method for reducing graphene oxide and organic silicon composite film is shown in FIG. Figure 1 and Figure 2 , the process of step 4 is as follows:
[0069] S4, cutting a ceramic tube, pre-treating the ceramic tube, and then coating a particle layer and an intermediate layer to obtain a ceramic support body.
[0070] like Figure 2 As shown, a certain length of ceramic tube is first cut. It should be noted that the figure is only an example, and the application does not limit the length of the ceramic tube cut.
[0071] Among them, the process of pre-treatment of ceramic tubes includes grinding and boiling.
[0072] It should be noted that during the production process, the ceramic tube may have defects such as burrs, holes or unevenness on the surface. These defects can be removed by grinding, and in the subsequent steps, other materials need to be coated on the surface of the ceramic tube. Grinding can increase the roughness of the surface, thereby improving the adhesion of the coating material. Then it is boiled in water, where boiling can effectively remove pollutants such as oil and dust on the surface of the ceramic tube, making the surface cleaner and tidier, and providing a good foundation for the subsequent adhesion of the coating particle layer and the intermediate layer.
[0073] Specifically, the ceramic tube adopts an α-Al2O3 asymmetric ceramic tube, which has a porous structure with a pore size of 200 to 220 nm;
[0074] The particle layer is aluminum oxide, the particle size in the particle layer is 0.2μm to 0.4μm, 4 to 5 layers are coated, the drying temperature is 200℃ to 220℃, the drying time is 20min to 30min, the calcination temperature is 520℃ to 580℃, and the calcination time is 20min to 25min.
[0075] The middle layer is a silica-zirconia particle sol, which is coated with 9 to 10 layers, and the calcination temperature is 520°C to 580°C, and the calcination time is 20 minutes to 25 minutes. The ceramic support is prepared by sequentially coating the particle layer and the middle layer on the ceramic tube. The particle layer and the middle layer can provide a good foundation for the subsequent attachment of the composite film.
[0076] S5. Apply the mixed sol on a ceramic support by rubbing method, and obtain reduced graphene oxide and organic silicon composite film after calcination.
[0077] Specifically, the mixed sol is diluted and then rubbed on the ceramic support by rubbing. The rubbing method is a hot coating method, the rubbing times are 2 to 3 times, the rubbing temperature is 150° C. to 200° C., the calcination time is 20 min to 30 min, and the coating thickness is 200 nm.
[0078] It should be noted that since the surface of the bridged organosilicon sol contains a large number of hydroxyl functional groups, it is easy to agglomerate in water to form an amorphous network structure, which affects the performance of the bridged organosilicon film. Therefore, the mixed sol is applied to a ceramic support by hot coating, and the mixed sol is quickly extended on the ceramic support, so that the solvent contained in the mixed sol can evaporate quickly, thereby forming a reduced graphene oxide and organosilicon composite film layer with uniform thickness and smooth surface, and a stable composite film can be formed after calcination.
[0079] The present application also provides a reduced graphene oxide and organic silicon composite film, which is prepared by the above-mentioned preparation method.
[0080] The inventors of the application have achieved the preparation of reduced graphene oxide and organic silicon composite film by strictly designing the content of each component and the parameters in each step. The method is introduced through various embodiments below.
[0081] Example 1
[0082] The reduction of graphene oxide and organic silicon composite film in this embodiment includes the following steps:
[0083] S11. Using a graphene oxide nano-dispersion liquid with a length of 5 um, the graphene oxide nano-dispersion liquid is placed in a blast drying oven for hydrothermal reduction reaction, the hydrothermal reduction reaction temperature is 200°C, the hydrothermal reduction reaction time is 2h, after the reaction is completed, a mixed solution is obtained, the mixed solution is washed with tetrahydrofuran and centrifuged to obtain reduced graphene oxide, wherein the centrifugal speed is 10000 rpm, the centrifugal time is 20min, and the number of centrifugal replacements is 2 times.
[0084] S12. Take reduced graphene oxide, hydroxymethyltriethoxysilane and hydrochloric acid in a mass ratio of 1:1:0.2, add the reduced graphene oxide and hydroxymethyltriethoxysilane to tetrahydrofuran, and then add hydrochloric acid to carry out a cross-linking reaction. The temperature of the cross-linking reaction is 70°C and the reaction time is 7h. Centrifuge and replace the solvent tetrahydrofuran in the mixed solution obtained after the cross-linking reaction with ethanol. The centrifugal speed is 8000r / min and the centrifugal time is 20min. After three replacements, a pre-cross-linked sol is obtained.
[0085] S13. According to the mass ratio of hydroxymethyltriethoxysilane, water and hydrochloric acid of 1:60:0.2, the pre-crosslinked sol and hydroxymethyltriethoxysilane are added into ethanol, and then water and hydrochloric acid are added to carry out hydrolysis condensation reaction. The temperature of the hydrolysis condensation reaction is 40°C and the reaction time is 2h. After the reaction, a mixed sol is obtained.
[0086] S14, intercepting a ceramic tube, grinding and boiling the ceramic tube, and then coating a particle layer and an intermediate layer to obtain a ceramic support. Among them, the ceramic tube is an α-Al2O3 asymmetric ceramic tube, the pore size of the porous structure of the ceramic tube is 200nm, the coated particle layer is alumina, the particle size in the particle layer is 0.2μm, 4 layers are coated, the drying temperature is 200℃, the drying time is 20min, the calcination temperature is 520℃, and the calcination time is 20min; the coated intermediate layer is a silica-zirconia particle sol, 9 layers are coated, the calcination temperature is 520℃, and the calcination time is 20min;
[0087] S15. Apply the mixed sol on the ceramic support by rubbing method, the rubbing times are 2 times, the rubbing temperature is 150° C., the calcination time is 20 min, the coating thickness is 200 nm, and after calcination, a reduced graphene oxide and organic silicon composite film is obtained.
[0088] Example 2
[0089] The reduction of graphene oxide and organic silicon composite film in this embodiment includes the following steps:
[0090] S21. Using a graphene oxide nano-dispersion liquid with a length of 6 um, the graphene oxide nano-dispersion liquid is placed in a blast drying oven for hydrothermal reduction reaction, the hydrothermal reduction reaction temperature is 210°C, the hydrothermal reduction reaction time is 4 hours, after the reaction is completed, a mixed solution is obtained, the mixed solution is washed with tetrahydrofuran and centrifuged to obtain reduced graphene oxide, wherein the centrifugal speed is 11000 rpm, the centrifugal time is 22 minutes, and the number of centrifugal replacements is 3 times.
[0091] S22. Take reduced graphene oxide, aminopropyltriethoxysilane and nitric acid in a mass ratio of 1:0.6:0.2, add the reduced graphene oxide and aminopropyltriethoxysilane to tetrahydrofuran, and then add nitric acid to carry out a cross-linking reaction. The temperature of the cross-linking reaction is 75°C, and the reaction time is 7.5h. The solvent tetrahydrofuran in the mixed solution obtained after the cross-linking reaction is centrifuged and replaced with ethanol, wherein the centrifugal speed is 6000r / min, the centrifugal time is 22min, and a pre-cross-linked sol is obtained after 4 replacements.
[0092] S23. According to the mass ratio of aminopropyltriethoxysilane, water and hydrochloric acid of 1:75:0.2, the pre-crosslinked sol and aminopropyltriethoxysilane are added into ethanol, and then water and nitric acid are added to carry out hydrolysis condensation reaction. The temperature of the hydrolysis condensation reaction is 45°C and the reaction time is 3 hours. After the reaction, a mixed sol is obtained.
[0093] S24, intercepting a ceramic tube, grinding and boiling the ceramic tube, and then coating a particle layer and an intermediate layer to obtain a ceramic support. Among them, the ceramic tube is an α-Al2O3 asymmetric ceramic tube, the pore size of the porous structure of the ceramic tube is 210nm, the coated particle layer is alumina, the particle size in the particle layer is 0.3μm, 4 layers are coated, the drying temperature is 210℃, the drying time is 22min, the calcination temperature is 550℃, and the calcination time is 22min; the coated intermediate layer is a silica-zirconia particle sol, 9 layers are coated, the calcination temperature is 550℃, and the calcination time is 22min;
[0094] S25. The mixed sol is rubbed on the ceramic support by rubbing method, the rubbing times are 2 times, the rubbing temperature is 175° C., the calcination time is 22 min, the rubbing thickness is 200 nm, and after calcination, a reduced graphene oxide and organic silicon composite film is obtained.
[0095] Example 3
[0096] The reduction of graphene oxide and organic silicon composite film in this embodiment includes the following steps:
[0097] S21. Using a graphene oxide nano-dispersion with a length of 7 um, the graphene oxide nano-dispersion is placed in a blast drying oven for hydrothermal reduction reaction, the hydrothermal reduction reaction temperature is 220°C, the hydrothermal reduction reaction time is 6 hours, and after the reaction is completed, a mixed solution is obtained, and the mixed solution is washed with tetrahydrofuran and centrifuged to obtain reduced graphene oxide, wherein the centrifugal speed is 11000 rpm, the centrifugal time is 25 minutes, and the number of centrifugal replacements is 2 times.
[0098] S22. Take reduced graphene oxide, 1,2-bis(triethoxysilyl)acetylene and sulfuric acid in a mass ratio of 1:0.8:0.2, add the reduced graphene oxide and 1,2-bis(triethoxysilyl)acetylene to tetrahydrofuran, and then add sulfuric acid for a cross-linking reaction. The temperature of the cross-linking reaction is 70°C and the reaction time is 7.5h. Centrifuge and replace the solvent tetrahydrofuran in the mixed solution obtained after the cross-linking reaction with ethanol. The centrifugal speed is 9000r / min and the centrifugal time is 25min. After 5 replacements, a pre-cross-linked sol is obtained.
[0099] S23. According to the mass ratio of 1,2-bis(triethoxysilyl)acetylene, water and hydrochloric acid of 1:80:0.1, the pre-crosslinked sol and 1,2-bis(triethoxysilyl)acetylene are added into ethanol, and then water and sulfuric acid are added to carry out hydrolysis condensation reaction. The temperature of the hydrolysis condensation reaction is 50°C and the reaction time is 4 hours. After the reaction, a mixed sol is obtained.
[0100] S24, intercepting a ceramic tube, grinding and boiling the ceramic tube, and then coating a particle layer and an intermediate layer to obtain a ceramic support. Among them, the ceramic tube is an α-Al2O3 asymmetric ceramic tube, the pore size of the porous structure of the ceramic tube is 220nm, the coated particle layer is alumina, the particle size in the particle layer is 0.4μm, 5 layers are coated, the drying temperature is 220℃, the drying time is 25min, the calcination temperature is 560℃, and the calcination time is 23min; the coated intermediate layer is a silica-zirconia particle sol, 9 layers are coated, the calcination temperature is 560℃, and the calcination time is 23min;
[0101] S25. The mixed sol is rubbed on the ceramic support by rubbing method, the rubbing times are 3 times, the rubbing temperature is 180° C., the calcination time is 25 min, the rubbing thickness is 200 nm, and after calcination, a reduced graphene oxide and organic silicon composite film is obtained.
[0102] Example 4
[0103] The reduction of graphene oxide and organic silicon composite film in this embodiment includes the following steps:
[0104] S21. Using a graphene oxide nano-dispersion liquid with a length of 8 um, the graphene oxide nano-dispersion liquid is placed in a blast drying oven for hydrothermal reduction reaction, the hydrothermal reduction reaction temperature is 240°C, the hydrothermal reduction reaction time is 8 hours, after the reaction is completed, a mixed solution is obtained, the mixed solution is washed with tetrahydrofuran and centrifuged to obtain reduced graphene oxide, wherein the centrifugal speed is 11000 rpm, the centrifugal time is 28 minutes, and the number of centrifugal replacements is 4 times.
[0105] S22. Take reduced graphene oxide, hydroxymethyltriethoxysilane and hydrochloric acid in a mass ratio of 1:1.2:0.2, add the reduced graphene oxide and hydroxymethyltriethoxysilane to tetrahydrofuran, and then add hydrochloric acid to carry out a cross-linking reaction. The temperature of the cross-linking reaction is 70°C and the reaction time is 7h. Centrifuge and replace the solvent tetrahydrofuran in the mixed solution obtained after the cross-linking reaction with ethanol. The centrifugal speed is 9000r / min and the centrifugal time is 25min. After 5 replacements, a pre-cross-linked sol is obtained.
[0106] S23. According to the mass ratio of hydroxymethyltriethoxysilane, water and hydrochloric acid of 1:80:0.2, the pre-crosslinked sol and hydroxymethyltriethoxysilane are added into ethanol, and then water and nitric acid are added to carry out hydrolysis condensation reaction. The temperature of the hydrolysis condensation reaction is 55°C and the reaction time is 3.5h. After the reaction, a mixed sol is obtained.
[0107] S24, intercepting a ceramic tube, grinding and boiling the ceramic tube, and then coating a particle layer and an intermediate layer to obtain a ceramic support. The ceramic tube is an α-Al2O3 asymmetric ceramic tube, the pore size of the porous structure of the ceramic tube is 200nm, the coated particle layer is alumina, the particle size in the particle layer is 0.4μm, 5 layers are coated, the drying temperature is 220℃, the drying time is 28min, the calcination temperature is 560℃, and the calcination time is 25min; the coated intermediate layer is a silica-zirconia particle sol, 10 layers are coated, the calcination temperature is 560℃, and the calcination time is 25min;
[0108] S25. The mixed sol is rubbed on the ceramic support by rubbing method, the rubbing times are 3 times, the rubbing temperature is 190° C., the calcination time is 28 min, the rubbing thickness is 200 nm, and after calcination, a reduced graphene oxide and organic silicon composite film is obtained.
[0109] Example 5
[0110] The reduction of graphene oxide and organic silicon composite film in this embodiment includes the following steps:
[0111] S51. Use a graphene oxide nano-dispersion with a length of 10 um, and place the graphene oxide nano-dispersion in a forced air drying oven for hydrothermal reduction reaction. The hydrothermal reduction reaction temperature is 250° C., and the hydrothermal reduction reaction time is 10 hours. After the reaction is completed, a mixed solution is obtained. The mixed solution is washed with tetrahydrofuran and centrifuged to obtain reduced graphene oxide, wherein the centrifugal speed is 12000 rpm, the centrifugal time is 30 minutes, and the number of centrifugal replacements is 3 times.
[0112] S52. Take reduced graphene oxide, hydroxymethyltriethoxysilane and hydrochloric acid in a mass ratio of 1:1.5:0.2, add the reduced graphene oxide and hydroxymethyltriethoxysilane to tetrahydrofuran, and then add hydrochloric acid to carry out a cross-linking reaction. The temperature of the cross-linking reaction is 80°C and the reaction time is 8h. The solvent tetrahydrofuran in the mixed solution obtained after the cross-linking reaction is centrifuged and replaced with ethanol. The centrifugal speed is 12000r / min and the centrifugal time is 30min. After 5 replacements, a pre-cross-linked sol is obtained.
[0113] S53. According to the mass ratio of hydroxymethyltriethoxysilane, water and hydrochloric acid of 1:90:0.1, the pre-crosslinked sol and hydroxymethyltriethoxysilane are added into ethanol, and then water and hydrochloric acid are added to carry out hydrolysis condensation reaction. The temperature of the hydrolysis condensation reaction is 60°C and the reaction time is 4 hours. After the reaction, a mixed sol is obtained.
[0114] S54, intercepting a ceramic tube, grinding and boiling the ceramic tube, and then coating a particle layer and an intermediate layer to obtain a ceramic support. The ceramic tube is an α-Al2O3 asymmetric ceramic tube, the pore size of the porous structure of the ceramic tube is 200nm, the coated particle layer is alumina, the particle size in the particle layer is 0.4μm, 5 layers are coated, the drying temperature is 220℃, the drying time is 30min, the calcination temperature is 580℃, and the calcination time is 25min; the coated intermediate layer is a silica-zirconia particle sol, 10 layers are coated, the calcination temperature is 580℃, and the calcination time is 25min;
[0115] S55. The mixed sol is rubbed on the ceramic support by rubbing method, the rubbing times are 3 times, the rubbing temperature is 200° C., the calcination time is 30 min, the rubbing thickness is 200 nm, and after calcination, a reduced graphene oxide and organic silicon composite film is obtained.
[0116] Comparative Example 1
[0117] The reduction of graphene oxide and organic silicon composite film in this embodiment includes the following steps:
[0118] S61. Use a graphene oxide nano-dispersion with a length of 5 um, and place the graphene oxide nano-dispersion in a forced air drying oven for hydrothermal reduction reaction. The hydrothermal reduction reaction temperature is 200°C, and the hydrothermal reduction reaction time is 2 hours. After the reaction is completed, a mixed solution is obtained. The mixed solution is washed with tetrahydrofuran and centrifuged to obtain reduced graphene oxide, wherein the centrifugal speed is 10,000 rpm, the centrifugal time is 20 minutes, and the number of centrifugal replacements is 2 times.
[0119] S62. Take reduced graphene oxide, hydroxymethyltriethoxysilane and hydrochloric acid in a mass ratio of 1:1:0.2, add the reduced graphene oxide and hydroxymethyltriethoxysilane to tetrahydrofuran, and then add hydrochloric acid to carry out a cross-linking reaction. The temperature of the cross-linking reaction is 70°C and the reaction time is 7h. Centrifuge the solvent tetrahydrofuran in the mixed solution obtained after the cross-linking reaction to replace it with ethanol, wherein the centrifugal speed is 8000r / min and the centrifugal time is 20min. After three replacements, a pre-cross-linked sol is obtained.
[0120] S63. According to the mass ratio of hydroxymethyltriethoxysilane, water and hydrochloric acid of 1:90:0.2, the pre-crosslinked sol and hydroxymethyltriethoxysilane are added into ethanol, and then water and hydrochloric acid are added to carry out hydrolysis condensation reaction. The temperature of the hydrolysis condensation reaction is 40°C and the reaction time is 2h. After the reaction, a mixed sol is obtained.
[0121] Comparative Example 2
[0122] The reduction of graphene oxide and organic silicon composite film in this embodiment includes the following steps:
[0123] S71. According to the mass ratio of hydroxymethyltriethoxysilane, water and hydrochloric acid of 1:60:0.2, the pre-crosslinked sol and hydroxymethyltriethoxysilane are added into ethanol, and then water and hydrochloric acid are added to carry out hydrolysis condensation reaction. The temperature of the hydrolysis condensation reaction is 40°C and the reaction time is 2h. After the reaction, a mixed sol is obtained.
[0124] S72, intercepting a ceramic tube, grinding and boiling the ceramic tube, and then coating a particle layer and an intermediate layer to obtain a ceramic support. The ceramic tube is an α-Al2O3 asymmetric ceramic tube, the pore size of the porous structure of the ceramic tube is 200nm, the coated particle layer is alumina, the particle size in the particle layer is 0.2μm, 4 layers are coated, the drying temperature is 200℃, the drying time is 20min, the calcination temperature is 520℃, and the calcination time is 20min; the coated intermediate layer is a silica-zirconia particle sol, 9 layers are coated, the calcination temperature is 520℃, and the calcination time is 20min;
[0125] S73, applying the mixed sol on a ceramic support by rubbing, the rubbing times are 2 times, the rubbing temperature is 150° C., the calcination time is 20 min, the coating thickness is 200 nm, and after calcination, an organic silicon composite film is obtained.
[0126] Comparative Example 3
[0127] The graphene oxide and organosilicon composite film in this embodiment includes the following steps:
[0128] S81. Take 1,2-bis(triethoxysilyl)acetylene, hydrochloric acid and water in a mass ratio of 1:0.2:60, add 1,2-bis(triethoxysilyl)acetylene and water to an ethanol solution and mix them evenly, then add sulfuric acid, and obtain an organosilicon polymer sol after hydrolysis and condensation reaction. The temperature of the hydrolysis and condensation reaction is 40°C and the time is 4h. The weight of 1,2-bis(triethoxysilyl)acetylene is 5% of the sum of the weights of 1,2-bis(triethoxysilyl)acetylene, hydrochloric acid, water and the alcohol solution.
[0129] S82, stirring and dispersing the graphene oxide nanosheets in water to obtain a dispersion with a concentration of 0.1 mg / ml, wherein the size of the graphene oxide nanosheets is 200 nm, and the stirring and dispersing time of the graphene oxide nanosheets is 10 min.
[0130] S83, uniformly dispersing the dispersion into the organosilicon polymer sol to obtain a mixed sol. The weight ratio of the graphene oxide nanosheets to the silicon source precursor is 0.5:1.
[0131] S84, intercepting a ceramic tube, pre-treating the ceramic tube, and then coating a particle layer and an intermediate layer to obtain a ceramic support. The ceramic tube is an α-Al2O3 asymmetric ceramic tube with a pore size of 200nm. The particle size in the particle layer is 0.2μm, 5 layers are coated, the drying temperature is 150℃, the drying time is 30min, the calcination temperature is 600℃, and the calcination time is 20min. The intermediate layer is a silica-zirconia particle sol, 10 layers are coated, the calcination temperature is 600℃, and the calcination time is 20min.
[0132] S85, applying the mixed sol on a ceramic support by rubbing, and obtaining an organic silicon composite film after calcination.
[0133] The water flux, salt rejection rate and stability of the reverse composite membranes of Examples 1 to 5 and Comparative Examples 1 to 4 were tested respectively. The results are shown in Table 1.
[0134] The water flux was detected in the following manner: the prepared composite membrane was measured under the same environment (25° C., 10000 ppm NaCl raw material solution, 1.0 MPa to 1.5 MPa).
[0135] The salt rejection rate was tested as follows: the conductivity of the solution on the permeate side and the raw material side of the prepared organic silicon composite membrane was measured under the same environment (25° C., 10000 ppm NaCl raw material solution, 1.0 MPa to 1.5 MPa).
[0136] Among them, water flux (Jv), water permeability (Lp), apparent retention rate (Robs), salt permeability flux (Js) and other parameters are usually used to evaluate the reverse osmosis performance of the membrane. The water flux (Jv) and water permeability (Lp) can be calculated through the following relationship:
[0137] L p =J v / ΔP-Δπ (1-1)
[0138] Δπ=C s RT (1-2)
[0139] R obs =(1-C p / C f )×100% (1-3)
[0140] J s =B(C f -C p ) (1-4)
[0141] It should be noted that J is the water flux, Lp is the water permeability, ΔP is the difference in applied pressure, Δπ is the difference in osmotic pressure; Δπ is the difference in osmotic pressure, C S is the molar concentration of the ion, R is the gas constant, and T is the absolute temperature; C f and C p are the salt concentrations in the feed and permeate, respectively; B is the salt permeability, C f and C p are the salt concentrations in the feed and permeate, respectively.
[0142] Table 1
[0143] Examples and Comparative Examples Water flux (L / (m2 h bar)) Salt retention rate (%) Example 1 7.3 97.4 Example 1 9.7 97.3 Example 1 8.1 97.3 Example 1 11.1 97.2 Example 1 7.0 97.6 Comparative Example 1 28.5 36.6 Comparative Example 2 6.3 96.2 Comparative Example 3 21.6 42.7
[0144] From the above test data, we can know that: Water flux and salt rejection performance of the composite membranes prepared in Examples 1 to 5 All higher than Comparative Examples 1 to 3 .
[0145] Figure 3 It is a surface SEM image of the reduced graphene oxide and the organosilicon composite film in the present invention.
[0146] Please refer to the attached Figure 3 Yes, the composite membrane prepared by the preparation method of the present application has a continuous membrane surface, almost no defects, and a complete structure.
[0147] Figure 4 It is a cross-sectional SEM image of the reduced graphene oxide and organosilicon composite film in the present invention.
[0148] Please refer to the attached Figure 4 From the cross section of the composite membrane, it can be seen that the particles on the membrane are the splash particles remaining when preparing the shooting samples, and the top layer of the cross section structure is the membrane separation layer.
[0149] Figure 5 This is a thermal stability test diagram of the reduced graphene oxide and organic silicon composite film in the present invention.
[0150] Please refer to Figure 5. The composite membrane prepared by the preparation method of the present application can maintain a high flux and a high dye retention rate even after 60 hours of operation under the premise of constant operating pressure, raw material liquid concentration and operating temperature, which proves the excellent durability of the composite membrane.
[0151] It is understandable that those skilled in the art can make equivalent substitutions or changes based on the technical solution and inventive concept of the present invention, and all these changes or substitutions should fall within the protection scope of the present invention.
Claims
1. A method for preparing a reduced graphene oxide and organosilicon composite film, characterized in that: The following steps are involved: Take reduced graphene oxide, a silicon source precursor and an acidic catalyst in a mass ratio of 1: (0.6-1.5): 0.2, add the reduced graphene oxide and the silicon source precursor into tetrahydrofuran, then add the acidic catalyst to carry out a cross-linking reaction, the temperature of the cross-linking reaction is 70° C.-80° C., the reaction time is 7h-8h, and the solvent tetrahydrofuran in the mixed solution obtained after the cross-linking reaction is replaced with an alcohol solution to obtain a pre-cross-linked sol; According to the mass ratio of silicon source precursor, water and acid catalyst of 1: (60-90): (0.1-0.2), the pre-crosslinked sol and the silicon source precursor are added into an alcohol solution, and then the water and the acid catalyst are added to carry out a hydrolysis condensation reaction, wherein the temperature of the hydrolysis condensation reaction is 40° C. to 60° C., the reaction time is 2 h to 4 h, and a mixed sol is obtained after the reaction; Cutting a ceramic tube, pre-treating the ceramic tube, and then coating a particle layer and an intermediate layer to obtain a ceramic support body; The mixed sol is rubbed on a ceramic support by a rubbing method, and is calcined to obtain a reduced graphene oxide and organic silicon composite film.
2. The method for preparing the reduced graphene oxide and organosilicon composite film according to claim 1, characterized in that: The preparation method of the reduced graphene oxide is as follows: The graphene oxide nano-dispersion liquid is placed in a drying device for hydrothermal reduction reaction. After the reaction is completed, a mixed solution is obtained. The mixed solution is washed with tetrahydrofuran and centrifuged to obtain the reduced graphene oxide.
3. The method for preparing the reduced graphene oxide and organosilicon composite film according to claim 2, characterized in that: The length of the graphene oxide in the graphene oxide nano-dispersion liquid is 5 um to 10 um.
4. The method for preparing the reduced graphene oxide and organosilicon composite film according to claim 3, characterized in that: The temperature of the hydrothermal reduction reaction is 200° C. to 250° C.; the time of the hydrothermal reduction reaction is 2 h to 10 h.
5. The method for preparing the reduced graphene oxide and organosilicon composite film according to claim 3, characterized in that: The centrifugal speed is 10000 rpm to 12000 rpm, the centrifugal time is 20 min to 30 min, and the number of centrifugal replacements is 2 to 3 times.
6. The method for preparing the reduced graphene oxide and organosilicon composite film according to claim 1, characterized in that: The silicon source precursor includes at least one of hydroxymethyltriethoxysilane, aminopropyltriethoxysilane and 1,2-bis(triethoxysilyl)acetylene; The acidic catalyst is any one of hydrochloric acid, sulfuric acid and nitric acid; The alcohol solution is any one of an ethanol solution and a n-propanol solution.
7. The method for preparing the reduced graphene oxide and organic silicon composite film according to claim 1, characterized in that: The replacement adopts a centrifugal replacement method, the centrifugal speed is 6000rpm to 12000rpm, the centrifugal time is 20min to 30min; the number of centrifugal replacements is 3 to 5 times.
8. The method for preparing the reduced graphene oxide and organosilicon composite film according to claim 1, characterized in that: The ceramic tube is an α-Al2O3 asymmetric ceramic tube, and the ceramic tube is a porous structure, and the pore size of the porous structure is 200-220nm; The pretreatment includes grinding and boiling the ceramic tube.
9. The method for preparing the reduced graphene oxide and organosilicon composite film according to claim 1, characterized in that: The particle layer is aluminum oxide, the particle size in the particle layer is 0.2 μm to 0.4 μm, 4 to 5 layers are applied, the drying temperature is 200° C. to 220° C., the drying time is 20 min to 30 min, the calcination temperature is 520° C. to 580° C., and the calcination time is 20 min to 25 min; The intermediate layer is a silica-zirconia particle sol, which is coated with 9 to 10 layers, calcined at a temperature of 520°C to 580°C, and calcined for 20 to 25 minutes; The rubbing coating method is a hot coating method, the rubbing times are 2 to 3 times, the rubbing temperature is 150° C. to 200° C., and the calcination time is 20 minutes to 30 minutes.
10. A reduced graphene oxide and organosilicon composite film, characterized in that: The reduced graphene oxide and organosilicon composite film is prepared by the method for preparing the reduced graphene oxide and organosilicon composite film according to any one of claims 1 to 9.
